The role of topical papaverine in microvascular surgery - Shah, Sankit D.; Rajgor, Darshil K.; Ghelani, Nilesh B.; Godhani, Chintan A.; Shah, Virank V.; Pathak, Nupoor H. (International Journal of Research in Medical Sciences, 2025)
Background: Intraoperative vasospasm during microvascular surgery can significantly impact surgical outcomes, leading to reduced blood flow and potential flap failure. This study evaluates the effects of local application of topical Papaverine, a nonspecific phosphodiesterase inhibitor, in enhancing vessel diameter, preventing vasospasm, and improving flap survival. A total of 1,000 microvascular anastomoses were analysed across multiple reconstruction types. Results showed an average of 66% increase in arterial diameter, reduced incidence of thrombus formation, and improvement in flap survival rates. Papaverine demonstrated immediate vasodilatory effects, solidifying its role as a gold-standard agent in microsurgery. Methods: A retrospective study evaluated 1,000 microvascular anastomoses performed in a single year. reconstruction such as head and neck, post-oncological, extremity, and digital re-implantations were included. Papaverine was sprayed topically over vessels. Vessel diameter changes were measured before and 10 minutes after application. Results: Significant improvement in vessel diameter following Papaverine application. Arterial diameter increased by an average of 66%, while venous dilation was observed at a 23% increase. Papaverine’s strong vasodilatory effects, particularly in arteries with higher smooth muscle content. The rapid onset of action (within 1–5 minutes) was consistent, ensuring immediate resolution of vasospasm. overall flap survival rate improved by 15%, and re-exploration rates decreased from 8% to 3%, emphasizing its role in enhancing surgical outcomes. Conclusions: Papaverine effectively prevents intraoperative vasospasm, enhances vessel diameter, and improves overall flap survival by reducing re exploration rates. These findings validate its role as a gold-standard vasodilator in microvascular surgery.